Synergistic and additive interactions of Shewanella sp., Pseudomonas sp. and Thauera sp. with chlorantraniliprole and emamectin benzoate for controlling Spodoptera litura (Fabricius) - Sunaina Sarkhandia; Geetika Sharma; Rohit Mahajan; Satish Koundal; Manoj Kumar; Pooja Chadha; Harvinder Singh Saini; Sanehdeep Kaur (Scientific Reports, 2023)
Abstract The imprudent use of insecticides causes the development of resistance in insect pest populations, contamination of the environment, biological imbalance and human intoxication. The use of microbial pathogens combined with insecticides has been proposed as an alternative strategy for insect pest management. This IPM approach may offer effective ways to control pests, in addition to lowering the risk of chemical residues in the environment. Spodoptera litura (Fabricius) is a major pest of many crops like cotton, maize, tobacco, cauliflower, cabbage, and fodder crops globally. Here, we evaluated the combined effects of new chemistry insecticides (chlorantraniliprole and emamectin benzoate) and entomopathogenic bacterial strains, Shewanella sp. (SS4), Thauera sp. (M9) and Pseudomonas sp. (EN4) against S. litura larvae inducing additive and synergistic interactions under laboratory conditions. Both insecticides produced higher larval mortality when applied in combination with bacterial isolates having maximum mortality of 98 and 96% with LC50 of chlorantraniliprole and emamectin benzoate in combination with LC50 of Pseudomonas sp. (EN4) respectively. The lower concentration (LC20) of both insecticides also induced synergism when combined with the above bacterial isolates providing a valuable approach for the management of insect pests. The genotoxic effect of both the insecticides was also evaluated by conducting comet assays. The insecticide treatments induced significant DNA damage in larval hemocytes that further increased in combination treatments. Our results indicated that combined treatments could be a successful approach for managing S. litura while reducing the inappropriate overuse of insecticides.